A Glance on Indoor Air Pollutants, their Impacts and Simple Solutions to Avoid Health Related Issues - Husainy, Avesahemad SN; Kulkarni, Shubham S; Rankhambe, Sudhanshu S; Haswal, Suraj S; Ambade, Bharatesh A; Pendhari, Asiya S (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 7 No 4 (2020): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2020)
Every coin has two sides. Likewise, as we are progressing towards the era of technology and industrialization; a lot of worst effects are arising as well. Along with the ecosystem, human health is suffering from some adverse issues because of pollution. We have heard about outdoor air pollution but indoor air pollution is even more harmful to human health. It is being observed that Indoor Air Quality (IAQ) is getting worse day by day leading to many lung diseases, breathing issues, low birth rate, eye-related diseases, perinatal conditions, etc. Hence these issues have to be considered before getting too late. Indoor air quality varies from regions i.e. in the case of developed countries; cooling-heating appliances, electric devices, petroleum products, etc. are the major contributors to deplete IAQ. While in case of developing countries which have a huge number of rural areas; biomass open fires, traditional cooking systems with direct fire expose or indoor stove, etc. are the major factors behind damaged indoor air quality. Generally, children and aged persons spend most of their time inside the house. These people have low immunity hence they get easily affected by depleted IAQ and face many health-related issues. There is a long list of harmful pollutants like NOX, COX, SOX, organic matter, etc. that play a significant role in damaging air quality. A ventilation system is essential in offices, theatres, malls, homes, etc. but the occupant devices lower the air quality index. Likewise, green-house effects increase the percentage of COX which damages nature and human health as well. All these factors, parameters, adverse effects and solutions are studied in this paper. How to cite this article:  Husainy ASN, Kulkarni SS, Rankhambe SS et al. A Glance on Indoor Air Pollutants, their Impacts and Simple Solutions to Avoid Health Related Issues. J Adv Res Alt Energ Env Eco 2020; 7(4): 1-9. DOI: https://doi.org/10.24321/2455.3093.202009